GAMBARAN GANGGUAN PSIKOLOGI IBU NIFAS DI KECAMATAN KALIGONDANG KABUPATEN PURBALINGGA TAHUN 2013 - Feti Kumala Dewi; Ari Hidayatun (Universitas Harapan Bangsa Purwokerto, 2013)
As many as 80% of women experience mood disturbances after pregnancy (childbirth). Probes pascanatal 6 weeks postnatal examination is an ideal opportunity for early detection ofpostnatal depression, but the sign is often overlooked. Based on the results of an interview with avillage midwife who were in the closest health center in the area of service kalikajar showed 1case of schizophrenia and 1 case of postnatal depression in 2012. How to know description physiology disorder mother postnatal in the area of serviceKalikajar Health Center in 2013. Using quantitative filter design is descriptive research approach with Cros sectional.Are the entire population of postnatal mother health center in the area of service Kalikajar theyear 2013. Mechanical Sampling was accidental sampling with survey respondents 30 postnatalmothers. The research instrument used was a questionnaire Edinburgh Postnatal Depresion scale(EPDS) and questionnaire about sign and symptoms of postnatal physiological disorders. The study by using the questionnaire on maternal postnatal EPDS more than 7 daysthere were 19 maternal postnatal (63.33%) who did not experience postnatal depression. Beingthe result of the questionnaires about sign and symptoms of physiological disorderspostnatal there are 18 postnatal mother (60%) did not experience postnatal psychologicaldisorders. There are some respondent no experience postnatal depression by EPDS and did notexperience postnatal psychological disorders by postnatal physiology sign and symptoms ofpostnatal physiological disorders. Keywords: Psychological Disorders, postnatal mother.